Transport economics - Blauwens, Gust, 1944-; De Baere, Peter, ....-; Van De Voorde, Eddy, 1955- (Berchem : De Boeck, 2016)
Transport economics has become a well-developed discipline with branches in many areas of economic science. Transport Economics combines four different perspectives in a single volume and to provide a general overview.
Keywords: Transport